Using biographical details as seductive information in a science text (Revista de Psicología, 2019)
This study examined the effect of including seductive details in an expository-structured scientific text. 66 low prior-knowledge students read the text without a seductive detail, or with an interesting biographic detail. Interestingness associated to the materials was pre-tested in a preliminary study. Post-reading memory (text recall and literal sentences verification task), comprehension (inferred sentences verification task), and synthesis capacity (title selection) were collected. Results revealed that the condition that read the biographic detail showed the poorest recall and the highest error rate in the verification of sentences related to the text segments adjacent to the detail. These results are interpreted considering the deviated integration hypothesis.
Keywords: comprehension; seductive detail; expository text